Water Hardness in the Eye of the Beholder: Exploring Links between Central Softening, Customer Perception and Behavior, and Citizen Science. (24th January 2022) - Brouwer, Stijn; Bouziotas, Dimitrios
Despite the significant growth of citizen science (CS) initiatives in number, scale, and scope, few studies have taken an empirical approach to studying the outcomes for individual participants. This paper analyzes these outcomes within the drinking water domain and assesses to what extent, if at all, CS participation leads to more profound perception and behavior change as compared with non-CS participation, i.e., the control group. Our empirical research is based around a CS project studying the hardness and lime deposition of drinking water in the Flemish Waarmaarde area, where, during the project period, water hardness was lowered through the installation of a central softener. The CS participants performed two hardness measurement rounds, both prior and following the softener installation. To monitor the difference in perception and behavior between CS participants and non-CS participants, both before and after this intervention, complementary quantitative surveys were conducted at three different stages (baseline and pre– and post–softener installation). The results showed that the central softening of water can lead to significant positive shifts in the perception of, among other factors, hardness, quality, and confidence in the water utility. For several factors, this shift is more profound among CS participants compared with the control group. The same pattern is observed when examining behavior, evidenced for instance in the frequency of use of calcium-removing products.